1973
DOI: 10.1351/pac197333020197
|View full text |Cite
|
Sign up to set email alerts
|

Steric aspects of the photochemistry of conjugated dienes and trienes

Abstract: The photochemical transformation of the 1 ,3-cyclohexadiene chromophore can Iead via orbital symmetry allowed pathways either to a bicyclo[2.2.0]hex-2-ene derivative or to a 1 ,3,5-hexatriene derivative. It was established that the ground state conformation of the starting 1 ,3-cyclohexadiene controls the primary photochemical reaction. The photoproducts composition can be changed by variation of the wavelength or of the temperature. The mechanisms of these processes are discussed. The photochemical transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(28 citation statements)
references
References 61 publications
(12 reference statements)
0
28
0
Order By: Relevance
“…The observation of products consistent with conrotatory motion for the photochemical ring closure of trienes 11 to 1,3-cyclohexadienes 9 and the reverse reaction [18], Fig. 5, implies that this reaction does not involve an SDSE process and thus it is not pericyclic in nature.…”
Section: 'mentioning
confidence: 74%
See 1 more Smart Citation
“…The observation of products consistent with conrotatory motion for the photochemical ring closure of trienes 11 to 1,3-cyclohexadienes 9 and the reverse reaction [18], Fig. 5, implies that this reaction does not involve an SDSE process and thus it is not pericyclic in nature.…”
Section: 'mentioning
confidence: 74%
“…Furthermore in the planar conformation it would have to compete with the concerted four isoelectron electrocyclisation which results in cyclobutene formation. Dauben et al have clearly shown that the nonplanar conformation favours ring opening and the planar or near planar conformation favours bicyclo[2.2.0]hex-2-ene formation [18]. Locking the molecules in the planar conformation and varying the wavelength of light in the photochemical reaction may result in the emergence of the concerted disrotatory pathway for the six isoelectron electrocyclisation over the four isoelectron electrocyclisation.…”
Section: 'mentioning
confidence: 99%
“…From these and a large number of other polycyclic cyclohexadiene systems, from temperature and wavelength dependences, Dauben et al concluded that the selection of the path is again controlled by the conformers [48]; and from inspection of the stereochemistry by X-ray diffraction or from conformational analysis by molecular models, they inferred that the conrotatory ring opening occurs most efficiently from the half-chair conformation with a C2-C3 twist angle around 20 or more, whereas the disrotatory ring closure to cylocbutenes takes place from nearly planar conformations with a C2-C3 twist angle of 10 or smaller (see [42,48,49]) (some authors [44,50] prefer the torsion of the C5-C6 single bond as a criterion for the ring puckering).…”
Section: Conrotatory Ring Opening Versus Disrotatory Ring Closurementioning
confidence: 98%
“…Also many of the bicyclic molecules of Scheme 4 give rise to ring closure besides ring opening [42,48]; also other derivatives show both reactions [48]. Cyclobutenes even prevail, if the fused ring is small (5-or 4-membered, see the example in Scheme 5) and/or stiff, or if one more ring is fused to the saturated C5-C6 bond (propellanes) [42].…”
Section: Conrotatory Ring Opening Versus Disrotatory Ring Closurementioning
confidence: 99%
See 1 more Smart Citation